Chloro-Furanocembranolides from Leptogorgia sp Improve Pancreatic Beta-Cell Proliferation - Gallardo Ovando, Amalia Beatriz; Diaz-Marrero, Ana R.; de la Rosa, Jose M.; D'Croz, Luis; Perdomo, German; Cozar-Castellano, Irene; Darias, Jose; Cueto, Mercedes (My University, 2018)
Two new chloro-furanocembranolides (1, 2) and two new 1,4-diketo cembranolides (3, 4) were isolated from the crude extract of Leptogorgia sp. together with a new seco-furanocembranolide (5) and the known Z-deoxypukalide (6), rubifolide (7), scabrolide D (8) and epoxylophodione (9). Their structures were determined based on spectroscopic evidence. Four compounds: 1, 2, 7 and 8 were found to activate the proliferation of pancreatic insulin-producing (beta) cells.
Keywords: leptogorgia; cembranolides; furanocembranolides; diketocembranolides; seco-furanocembranolides; chloro-furanocembranolides; pancreatic beta-cells